Ruptured hepatocellular carcinoma presenting as Cullen’s and Grey-Turner’s sign (Indian Journal of Case Reports, 2020)
Hepatocellular carcinoma (HCC), the most common malignant liver tumor, is usually asymptomatic but rarely bleeds into the peritoneal cavity which can be a serious catastrophe. In this case report, we are presenting a case of ruptured HCC, who came to our emergency room with hepatic decompensation in the form of jaundice and progressive abdominal distention and on evaluation were found to have ruptured HCC and the classical findings associated with it were the signs of intraperitoneal bleed like Cullen’s and Grey-Turner’s sign which are classically mentioned in acute pancreatitis.